2002
DOI: 10.1136/ard.61.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Circulating soluble E-selectin in early rheumatoid arthritis: a prospective five year study

Abstract: Background: Soluble E-selectin (sE-selectin) is a marker of activation of vascular endothelium. Objective: To examine serum levels of sE-selectin in a cohort of 85 patients with early rheumatoid arthritis (RA) followed up for five years. Methods: sE-selectin levels were assessed annually using an enzyme linked immunosorbent assay (ELISA) and related to simultaneously obtained clinical and laboratory measures. Joint inflammation was evaluated by active joint count, functional status by Health Assessment Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…P‐ and E‐selectin expressed on activated endothelial cells mediate rolling and emigration of leukocytes, including T cells, from blood at sites of inflammation (15, 20). Soluble forms of P‐ and E‐selectin shed by endothelium are increased in the blood and SF in RA and JIA, and levels of soluble E‐selectin are correlated with other markers of disease activity (22–24). Ligands for P‐ and E‐selectin on activated T cells are generated by the induction of fucosyl transferase IV and VII (20, 27, 34, 44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P‐ and E‐selectin expressed on activated endothelial cells mediate rolling and emigration of leukocytes, including T cells, from blood at sites of inflammation (15, 20). Soluble forms of P‐ and E‐selectin shed by endothelium are increased in the blood and SF in RA and JIA, and levels of soluble E‐selectin are correlated with other markers of disease activity (22–24). Ligands for P‐ and E‐selectin on activated T cells are generated by the induction of fucosyl transferase IV and VII (20, 27, 34, 44).…”
Section: Discussionmentioning
confidence: 99%
“…The selectins are involved in the capture of leukocytes from the blood and their subsequent migration into tissue (15, 20). In both RA and JIA, P‐ and E‐selectin are up‐regulated on synovial blood vessels and their soluble forms are elevated in blood (21–24). These adhesion molecules likely are important in the recruitment of T cells to the joints in RA and JIA, as demonstrated in experimental arthritis (25, 26).…”
mentioning
confidence: 99%
“…In this study, sE-sel levels were similar among RD patients, their subgroups, and controls. Some previous studies have reported higher sE-sel levels in RD [23], as well as a reduction following anti-inflammatory treatment [24], whilst others have not shown significant differences [21,25]. In a longitudinal study, sE-sel did correlate with CRP, and was predictive of adverse radiological findings after 5 years [25].…”
Section: Discussionmentioning
confidence: 72%
“…[29] The latter group of studies that failed to find associations between patients with RA and controls all employed a cross-sectional study design and had examined patients with chronic RA. [30] In this study, the sE-selectin level was not significantly elevated in patients with hemophilia A. This might be because in our analyses, we did not stratify patients on the basis of the severity of hemophilic arthropathy (i.e., acute and chronic inflammation).…”
Section: Discussionmentioning
confidence: 73%